Constitutional Philosophy: The Basic Foundation of the Legal State - Yunus, Nur Rohim (ADALAH, 2023)
This essay examines the role of the constitution as a fundamental element in forming a democratic and just state based on law. In the philosophical dimension, the constitution is seen not only as a legal document but also as a reflection of fundamental values that reflect the identity of a nation, such as justice, freedom, and respect for human rights. This essay explains that a state based on law prioritises the supremacy of law, where all government actions must be based on the law, not the power of specific individuals or groups. According to legal philosophy, an ideal constitution must regulate the separation of powers, checks and balances mechanisms, and protection of citizens' rights. This essay also discusses the challenges that arise if a country does not have a strong constitution, which has the potential to cause legal uncertainty and political instability, and provides recommendations for strengthening the constitution in building a just state based on law.